Android control for an RTOS-based Pololu robot - Goh, Hung Meng (2016)
Embedded systems came into the limelight with the birth of microcontrollers and have been introduced into nearly all aspects of everyday life. Most electronic gadgets we use involves embedded systems. As embedded applications increase in complexity, the use of an operating system brings in numerous advantages. Most embedded systems have real time operating systems which allow them to make real time response in a timely manner. With the advent of the “Smart Nation” initiatives, secondary schools are starting to introduce computing as a subject. This will expose students to basic programming fundamental and prepare them for the future. The goal of the project was to develop a rapid embedded development platform to educate students on embedded system development and introduces basic programming knowledge via a hands on exercise in developing a remote control robot with minimal programming experience required. The m3pi robot and the mbed NXP LPC 1768 development board was used to provide a quick platform for learning about embedded application. Its online compiler coupled together with drag and drop functions allow amateurs to develop their own embedded application easily. MIT App Inventor, a web based builder that uses visual block language was used to develop the android application to control the robot. Its simple interface allows even a novice with minimal programming knowledge to develop a fully functional android application within a few hours. The real time operating system concept was implemented to the robot for it to perform multi-threading operations.